DESIGN A MONITORING AND AUTOMATION SYSTEM FOR DRINKING WATER FILLING WITH VOICE COMMANDS USING GOOGLE ASSISTANT - Manalu, Madoni Eprahim; Saleh, Muhammad; Priyatman, Hendro (Faculty of Engineering, Universitas Tanjungpura, 2024)
Drinking water filling stations currently still use faucets or buttons to stiffen drinking water filling, where the user is sometimes negligent which results in water overflow during the drinking water filling process and the availability of gallons of water at drinking water filling stations also often runs out. The purpose of this study is to monitor the availability of gallons of water at drinking water filling stations and fill drinking water with voice commands according to the desired water volume using Google Assistant. The command code given is